Intelligent Patient's Guide to the Doctor-Patient Relationship : Learning How to Talk So Your Doctor Will Listen. - Korsch, Barbara M. (Oxford University Press, 1998)
Do you feel that your doctor doesn't pay attention to what you say? Does your doctor cut you off when you try to explain how you feel? Do you think your doctor could remember your name without referring to your chart? Does your doctor seem to be in such a hurry that you don't even get a chance to ask your most important questions? Do you spend more time waiting than actually talking to your doctor? Do you understand what your doctor says? At one time or another, we have all had these complaints. This book will teach you how to ask the right questions, understand the answers, and show you how t.